1979
DOI: 10.1002/pssa.2210510227
|View full text |Cite
|
Sign up to set email alerts
|

Separate measurements of dynamical and kinematical X-ray diffractions from silicon crystals with a triple crystal diffractometer

Abstract: A, 1 1~s~) arid K. KOHRA The kinematical and dynaniical component's of diffracted X-rays from perfect and mechanically dsinsged silicon single crystals are separately measured in t.he vicinity of the reciprocal lattice point using a triple crystal arrangement of ( j -n , --n, +n) setting. I n the case of a perfect' crystal, besides the normal dynamical diffraction, a broad and weak hump due to the lattice vibration is observed a t the scattering vector deviation as small as 2 x lo3 cni-l. For crystals with lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0
3

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(78 citation statements)
references
References 12 publications
1
74
0
3
Order By: Relevance
“…In general, for crystals with moderate absorption the one-dimensional character of the rocking curve is able neither to distinguish between primary and secondary extinction effects (Zachariasen, 1965) nor to give information on the distribution of misorientations in directions, other than the normal to diffracting planes. Using triple-crystal diffractometry, Iida & Kohra (1979) and Wang & Matyi (1992) have shown that the diffracted intensity can be separated into its dynamical (coherent) and kinematical (incoherent) components. It is possible due to an extra angular dimension added to the diffraction process by the rotation angle of a highly perfect analyzer crystal.…”
Section: Introductionmentioning
confidence: 99%
“…In general, for crystals with moderate absorption the one-dimensional character of the rocking curve is able neither to distinguish between primary and secondary extinction effects (Zachariasen, 1965) nor to give information on the distribution of misorientations in directions, other than the normal to diffracting planes. Using triple-crystal diffractometry, Iida & Kohra (1979) and Wang & Matyi (1992) have shown that the diffracted intensity can be separated into its dynamical (coherent) and kinematical (incoherent) components. It is possible due to an extra angular dimension added to the diffraction process by the rotation angle of a highly perfect analyzer crystal.…”
Section: Introductionmentioning
confidence: 99%
“…The independent variation of the two diffraction angles ͑between incident x-rays and sample surface͒ and 2 ͑be-tween incident and scattered x-rays͒ provides the possibility of reciprocal space mapping, i.e., the acquisition of twodimensional projections in the three-dimensional reciprocal space. 6,7 The lateral macroperiodicity of the wire and dot arrays gives rise to lateral intensity maxima ͑wire satellites W i and dot satellites D i ) in the diffraction pattern. In principle, the full information about the geometrical shape ͑height, width, inclination of the sidewalls, period͒ as well as about the structural quality ͑strain and crystalline damage͒ can be obtained from a two-dimensional map of reciprocal space.…”
Section: Methodsmentioning
confidence: 99%
“…The other streak at an angle of about 10 ° with the ~0/20 axis is due to the increased lattice parameter after the ion-implantation. Using the formulae given by Iida and Kohra [33], this can be transformed in reciprocal space into an angle with the qx axis of 18 °, where the qx axis is parallel to the ¢o/20 axis [34]. This is equal to the angle that the (026) vector makes with the (001) vector perpendicular to the wafer surface.…”
Section: Methodsmentioning
confidence: 99%